Isolation of alkaloids compound of ethanol extract of mangrove perepat (S. alba) root and its antibacterial activity - Madyawati Latief; Muhaimin Muhaimin; Hilda Amanda; Indra Lasmana Tarigan; Siti Aisyah (Universitas Islam Indonesia, 2021)
Abstract Background: Exploration of the chemical contents and bioactivities of mangrove plants is important to discover new therapeutic agents for society and to develop its medicinal values.Objective: This study aims to isolate alkaloid compounds from the ethanol extract of Sonneratia alba root which is likely to have an antibacterial activity.Methods: Isolation was carried out using fractionation and chromatography, while antibacterial activity test was performed using the disc diffusion methods.Results: Our phytochemical screening shows that the ethanol extract has a high concentration of alkaloid compounds. The alkaloid which contain in isolate (F4) is further confirmed through UV-Vis Spectra and FT-IR spectra. The ethanol extract exhibits the antibacterial activity against S. aureus and E. coli with the inhibition zone of 1.5 mm and 2.5 mm, respectively.Conclusion: Alkaloid compound has been isolated from Sonneratia alba and has potential as antibacterial agent.Keywords: mangrove perepat (Sonneratia alba), alkaloid, antibacterial agent Intisari Latar Belakang: Eksplorasi kandungan kimiawi dan bioaktivitas tanaman mangrove penting dilakukan untuk menemukan agen terapeutik baru bagi masyarakat serta mengembangkan nilai medisnya.Tujuan: Penelitian ini bertujuan untuk mengisolasi senyawa alkaloid dari ekstrak etanol akar Sonneratia alba yang berpotensi menghasilkan aktivitas antibakteri.Metode: Isolasi senyawa dilakukan dengan fraksinasi dan kromatografi, sedangkan antibakteri dilakukan dengan metode difusi cakram.Hasil: Hasil skrining fitokimia yang telah dilakukan menunjukkan bahwa ekstrak etanol memiliki kandungan alkaloid yang tinggi. Kandungan alkaloid dalam Isolat (F4) telah dikonfirmasi secara spektrofotometri UV-Vis dan FT-IR. Aktivitas antibakteri ekstrak etanol terhadap S. aureus dan E. coli ditunjukkan dengan dihasilkannya zona hambat sebesar 1,5 mm dan 2,5 mm.Kesimpulan: Senyawa alkaloid berhasil diisolasi dari Sonneratia alba serta memiliki potensi sebagai agen antibakteri.Kata Kunci: mangrove perepat (Sonneratia alba), alkaloid, antibakteri